The Threat of COVID-19 and Job Insecurity Impact on Depression and Anxiety: An Empirical Study in the USA - Obrenovic, Bojan; Du, Jianguo; Godinic, Danijela; Baslom, Mohammed Majdy M; Tsoy, Diana (Frontiers in Psychology, 2021)
As the coronavirus disease 2019 pandemic causes a general concern regarding the overall mental health of employees worldwide, policymakers across nations are taking precautions for curtailing and scaling down dispersion of the coronavirus. In this study, we conceptualized a framework capturing recurring troublesome elements of mental states such as depression and general anxiety, assessing them by applying standard clinical inventory. The study explores the extent to which danger control and fear control under the Extended Parallel Processing Model (EPPM) threat impact job insecurity, with uncertainty phenomenon causing afflicting effect on the experiential nature of depression heightened by anxiety. With the aim to explore the job insecurity relationship with anxiety and depression, and measure the impact of EPPM threat, an empirical study was conducted in the United States on a sample of 347 white collar employees. Demographic data, EPPM threat, job insecurity, anxiety, and depression data were collected via a standardized questionnaire during the coronavirus disease 2019 (COVID-19) pandemic. The questionnaire consisting of multi-item scales was distributed online. All the scale items were evaluated on a 5-point Likert scale. SEM software AMOS version 23 was used to perform confirmatory factor analysis with maximum likelihood estimation. In the structural model, relationships between the threat of COVID-19, job insecurity, anxiety, and depression were assessed. The findings of the study suggest that job insecurity has a significant impact on depression and anxiety, whereas the threat of COVID-19 has a significant impact on depression. Mediating effects of job insecurity and EPPM threat impact on anxiety were not established in the study. The study contributes to the apprehension of the repercussions of major environmental disruptions on normal human functioning, and it investigates the effects of self-reported protective behaviors on risk perception. The study also explains the underlying mechanisms of coping behavior as possible antecedents to mental disorders. When subjected to stressful events, heightened psychological arousal causes physical and psychological challenges of affected employees to manifest as behavioral issues.